Pengaruh Work-Life Balance Terhadap Kinerja Karyawan: Studi Literatur Pada Era Kerja Fleksibel - Anisa Aulia Dewi (Jurnal Mahasiswa Manajemen, 2025)
Background – Flexible work systems in the post-pandemic kece slot era have increased attention to work-life balance (WLB) due to its impact on employee performance and well-being. Objective – This study kece slot aims to analyze the effect of work-life balance on employee performance in flexible work settings. Design / Methodology / Approach – A literature review was conducted by analyzing 30 national and international journal articles published between 2022 and 2025. Findings – The findings indicate that kece slot work-life balance positively influences employee performance, job satisfaction, and organizational commitment, although flexible work may lead to digital fatigue and work overload. Research Implication – The results provide insights for organizations in developing flexible work policies that support employee well-being and performance.